Conjunctive Use of Rain and Groundwater in Pearl Millet
Unless affected by a severe drought similar to that of 1987 and 002, crops in arid Rajasthan usually fail for want of 20 to 25 mm of rain, especially a the fag end of the season. This happened in 2005 cropping season. As there are fertile lCkets (oasis), due to the presence of water, scattered over the region, crop failure can e averted by way of groundwater supplementation to precipitation. In 1996, for instanc , pearl millet yield was 1725 kg ha-1 from rain alone, and when supplemented with 68, 179 and 204 mm of groundwater, crop yields improved to 2466, 3424 and 3615 kg ha- , respectively. Data for the 1998 season further revealed the significance of rain-groundwat r conjunctive use. Combining suboptimal Crop Water Supply (CWS:256 mm rain + 60 mn